PENGARUH PERTUMBUHAN PENDUDUK, ANGKA PARTISIPASI SEKOLAH DAN TINGKAT PARTISIPASI ANGKATAN KERJA TERHADAP PERTUMBUHAN EKONOMI PADA 5 PROVINSI DI INDONESIA - Riska Mulya Shari; Jariah Abubakar (Jurnal Ekonomi Regional Unimal, 2022)
This study examined the effect of population growth, school enrollment rate, and labor force participation rate on economic growth in five provinces in Indonesia, namely South Sulawesi, DI Yogyakarta, Gorontalo, North Maluku, and South Sumatra. This study used cross-section data of five provinces in Indonesia and time-series data during 2005-2020. The analysis method used was panel data with the help of E-Views10. The results partially showed that population growth positively and significantly influenced economic growth in five provinces in Indonesia, school participation rates did not negatively affect economic growth in five provinces in Indonesia, and labor force participation rates negatively affected economic growth in five provinces in Indonesia. Simultaneously, population growth, school enrollment rate, and labor force participation rate positively and significantly influenced economic growth in five provinces in Indonesia.